Aerogel film and forming method thereof

By using a polymer auxiliary film coated with silicone oil and clamping and curing with gradient heating during the aerogel film molding process, the problems of adhesion, scratches and solvent volatility during the aerogel film molding process are solved, and the high quality and thickness uniformity of the aerogel film are achieved.

CN120383761APending Publication Date: 2025-07-29IBIH ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510597108.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

The existing aerogel film molding methods have problems such as adhesion, scratches, solvent volatility affecting performance and environmental pollution, resulting in unstable product quality and uneven thickness.

Method used

Two layers of polymer auxiliary film coated with silicone oil are used to clamp the aerogel slurry for coating and molding, and are cured by gradient heating to avoid direct contact with the scraper or roller, reduce solvent volatility, and ensure structural stability and uniformity.

Benefits of technology

The structural consistency and stability of the aerogel film surface is achieved, adhesions and scratches are avoided, solvent volatility is reduced, material performance and working environment are ensured, product quality and thickness uniformity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005394898270000101
    Figure BDA0005394898270000101
  • Figure BDA0005394898270000111
    Figure BDA0005394898270000111
  • Figure BDA0005394898270000112
    Figure BDA0005394898270000112
Patent Text Reader

Abstract

The invention relates to the technical field of aerogel materials, and discloses an aerogel film and a forming method thereof.The method comprises the steps that 1, aerogel slurry is introduced between two layers of polymer auxiliary films for coating forming, and an intermediate material I is obtained; the polymer auxiliary film is obtained by coating the surface of a polymer film with silicone oil, and the surface coated with the silicone oil is in direct contact with the aerogel slurry; (2) curing the intermediate material I; the release force of the polymer auxiliary film is 15 to 50g / cm; the light transmittance of the polymer auxiliary film is 75%-95%, and the tensile strength of the polymer auxiliary film is 50-150 MPa. The technical scheme provided by the invention is suitable for large-scale and continuous production of the aerogel film, the operation is simple and convenient, and the prepared aerogel film product is more stable in quality and uniform in thickness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aerogel materials, and particularly relates to an aerogel film and a forming method thereof. Background Art

[0002] The forming method of the aerogel film directly affects its pore structure, mechanical properties, thickness uniformity, and large-scale production capacity. Currently, the forming methods of the aerogel film include various forming methods such as dip coating method, spin coating method, spraying method, roll coating method, doctor blade coating method, etc. The dip coating method is suitable for flexible substrates and can prepare ultra-thin and uniform film materials. However, the single coating thickness is limited, and multiple dips are required to increase the thickness. The peeling of the substrate may damage the aerogel structure. The spin coating method forms a uniform film with controllable thickness, but it is only suitable for small-area high-precision applications, and the material utilization rate is low (most of the sol is thrown out). The spraying method is suitable for substrates with complex shapes and can be continuously produced, but the porosity is relatively low, the solvent volatilizes quickly, and the gel structure is imperfect.

[0003] The doctor blade coating method and the roll coating method are widely used due to their advantages of controllable thickness, good uniformity, low cost, and simple operation. However, during the coating and forming process of the aerogel film using the doctor blade coating method or the roll coating method, the aerogel film material liquid directly contacts the doctor blade or the coating roll, thus sticking to the coating facility. The material liquid on it will gel within a certain period of time. When continuing to apply the coating, scratches on the material liquid and local non-uniformity will occur. Moreover, during the process of gradually forming the aerogel film from the aerogel slurry, especially after entering the curing line, the solvent volatilizes due to the influence of temperature, which not only affects the material performance but also pollutes the working environment. Summary of the Invention

[0004] The purpose of the present invention is to provide a forming method of an aerogel film with stable product quality and uniform thickness.

[0005] To achieve the above purpose, the first aspect of the present invention provides a forming method of an aerogel film, which includes:

[0006] (1) Introducing the aerogel slurry between two layers of polymer auxiliary films for coating and forming to obtain an intermediate material I; the polymer auxiliary film is obtained by coating silicone oil on the surface of a polymer film, and the side coated with silicone oil is in direct contact with the aerogel slurry;

[0007] (2) Curing the intermediate material I;

[0008] The release force of the polymer auxiliary film is 15 - 50 g / cm;

[0009] The light transmittance of the polymer auxiliary film is 75% - 95%, and the tensile strength is 50 - 150 MPa.

[0010] The second aspect of the present invention provides an aerogel film prepared by the method described in the foregoing first aspect.

[0011] The technical solution provided by the present invention has at least the following advantages:

[0012] (1) The technical solution provided by the present invention ensures the consistency and uniformity of the structures of the upper and lower surfaces of the aerogel film; the polymer auxiliary film treated with silicone oil can enable the aerogel film to be well separated from the polymer auxiliary film, avoiding tearing, thinning, etc. of the aerogel film caused by adhesion between the aerogel film and the polymer auxiliary film.

[0013] (2) In the technical solution provided by the present invention, the aerogel film is located between two auxiliary films, which avoids the solvent volatilization caused by temperature after entering the curing line in the later stage and affects the performance of the material; the aerogel film is located between two auxiliary films, which can effectively reduce the volatilization of organic solvents. On the one hand, it ensures the stability of the material structure and does not cause the collapse of the pore structure due to solvent volatilization. On the other hand, it creates a good working environment for experimental personnel.

[0014] (3) The technical solution provided by the present invention avoids the direct contact between the aerogel slurry and the doctor blade or coating roller, preventing the gel from sticking to the coating tool and causing scratches, local non-uniformity, etc. on the liquid during continuous coating.

[0015] (4) In the technical solution provided by the present invention, a polymer auxiliary film with silicone oil coated on its surface is used to assist in the formation of the aerogel film. The silicone oil has good chemical compatibility with the polymer film, and the silicone oil has a low surface tension and good coating performance, and can be uniformly coated on the surface of the polymer film to form a continuous and flat release layer, avoiding local adhesion to the surface of the polymer film during the preparation of the aerogel film and causing defects in the film. Detailed Embodiments

[0016] In the ranges disclosed herein, the endpoints and any values are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values and individual point values of each range, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0017] It should be noted that in various aspects of the present invention, for the same components or terms in each aspect, the present invention only describes them once in one aspect without repeating the description. Those skilled in the art should not understand this as a limitation of the present invention.

[0018] As described above, the first aspect of the present invention provides a method for forming an aerogel film, and the method includes:

[0019] (1) Introduce the aerogel slurry between two layers of polymer auxiliary films for coating and forming to obtain intermediate material I; the polymer auxiliary film is obtained by coating silicone oil on the surface of a polymer film, and the side coated with silicone oil is in direct contact with the aerogel slurry;

[0020] (2) Cure the intermediate material I;

[0021] The release force of the polymer auxiliary film is 15 - 50 g / cm;

[0022] The light transmittance of the polymer auxiliary film is 75% - 95%, and the tensile strength is 50 - 150 MPa.

[0023] In the present invention, the aerogel slurry is introduced between two layers of polymer auxiliary films for coating and forming. Particularly, a polymer auxiliary film that meets the release force requirement is used, and a polymer film with a light transmittance and tensile strength within a specific range is selected. The prepared aerogel film product not only has a uniform thickness, but also the structural consistency and stability of both surfaces of the film product are greatly improved, and at the same time, the optical properties of the aerogel film product are not affected.

[0024] Preferably, the release force of the polymer auxiliary film is 20 - 40 g / cm. Under this more preferred condition, the aerogel slurry can be completely formed on this polymer auxiliary film without forming defects, and when the sol-gel forms a wet gel, it can be completely peeled off from this polymer film without causing the film to be thinned or torn due to excessive force.

[0025] The bond energy of the silicon-oxygen bond (Si-O) in silicone oil is relatively high, making the organosilicone oil have good thermal stability and can maintain stable performance within a wide temperature range. For example, it can be used at -50°C to 200°C or even higher temperatures and is not easily decomposed and oxidized at high temperatures. Silicone oil does not react chemically with the polymer film to affect the release effect or the performance of the polymer film and can resist the erosion of chemical substances. The present invention does not particularly limit the specific type of the silicone oil, and those skilled in the art can select according to the known types of silicone oil in the art. Exemplarily, the silicone oil is polysiloxane-based silicone oil, which can be methyl silicone oil, ethyl silicone oil or phenyl silicone oil.

[0026] Preferably, the thickness of the polymer film is 50 - 150 μm, preferably 70 - 120 μm.

[0027] In some preferred embodiments of the present invention, a polymer auxiliary film with silicone oil coated on one side is used, and the side coated with silicone oil is in direct contact with the aerogel slurry for the coating and forming operation.

[0028] In the present invention, the surface energy of the single-sided silicone oil coating is moderate and relatively low, which is conducive to the spreading of the aerogel slurry on its surface. At the same time, after the preparation of the aerogel film is completed, it can ensure that the aerogel film and the polymer auxiliary film have appropriate separability, facilitating the subsequent film peeling operation.

[0029] The present invention has no particular limitation on the source or preparation process of the polymer auxiliary film. It can be obtained commercially, customized from a manufacturer according to actual needs, or prepared by known technical means in the art. The present invention will not elaborate herein, and those skilled in the art should not consider it as a limitation to the present invention.

[0030] In some embodiments, the aerogel slurry is a polyimide aerogel film slurry.

[0031] The present invention has no particular limitation on the preparation method of the aerogel slurry. Those skilled in the art can select according to known technical means in the art. The present invention exemplarily provides a preferred specific embodiment hereinafter, and those skilled in the art should not consider it as a limitation to the present invention.

[0032] Preferably, the viscosity of the aerogel slurry is 500 - 12000 mPa·S; for example, it can be 500 mPa·S, 1000 mPa·S, 2000 mPa·S, 3000 mPa·S, 4000 mPa·S, 5000 mPa·S, 6000 mPa·S, 7000 mPa·S, 8000 mPa·S, 9000 mPa·S, 10000 mPa·S, 11000 mPa·S, 12000 mPa·S or any value between 500 - 12000 mPa·S. The viscosity described in the present invention is measured at 25°C.

[0033] Preferably, the polymer film is selected from at least one of PET film, PP film, PTFE film, PE film, PPS film, and PI film, and more preferably PET film. The inventors found in the research that the polymer film type under the preferred conditions is not prone to swelling or dissolution when contacting with the aerogel slurry, has high transparency, is smooth and has good corrosion resistance, and the surface structure consistency and thickness uniformity of the prepared aerogel film are higher.

[0034] In the present invention, PET film refers to polyester film, PP film refers to polypropylene film, PTFE film refers to polytetrafluoroethylene film, PE film refers to polyethylene film, PPS film refers to polyphenylene sulfide film, and PI film refers to polyimide film.

[0035] Preferably, in step (1), the coating and forming method is a doctor blade coating method and / or a roll coating method.

[0036] According to a preferred specific embodiment, in step (1), the temperature of the coating and forming is -8°C to 25°C, preferably -5°C to 20°C, more preferably -5 to 5°C.

[0037] Preferably, in step (1), the coating speed of the coating and forming is 0.3 - 10 m / min. For example, it can be 0.3 m / min, 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min, 10 m / min or any value between 0.3 - 10 m / min.

[0038] The present invention can reasonably select the coating speed and coating pressure according to the viscosity, solid content of the aerogel slurry and the target coating thickness, preferably controlled by a pressure sensor and a regulating device. For low-viscosity coatings, the speed can be appropriately increased, while for high-viscosity coatings, the speed needs to be decreased.

[0039] In some embodiments, the method of the present invention may further include: before performing the coating and forming, cleaning the required coating tools to avoid impurities affecting the coating effect.

[0040] In some embodiments, the method of the present invention may further include: before performing the coating and forming, according to the target coating thickness, roughly adjusting the gap between the comma knife and the coating roll with a mechanical or electric device, and then calibrating it with a feeler gauge or a laser thickness measuring instrument to make the gap accuracy reach ±0.01 mm.

[0041] According to another preferred specific embodiment, in step (2), the curing treatment adopts a gradient heating method, and the temperature interval between adjacent gradients is 5 - 10°C.

[0042] Preferably, in step (2), the end temperature of the curing treatment is 60 - 70°C, and the treatment time for each temperature gradient is independently selected from 3 - 10 min.

[0043] Adopting the gradient heating method under the preferred conditions of the present invention can improve the microstructural uniformity of the polyimide aerogel film product and obtain a film product with more excellent mechanical properties and transparency.

[0044] Preferably, the method of step (2) of the present invention further includes: subjecting the intermediate material I to a curing treatment to obtain an intermediate material II, and then winding up, aging, solvent replacement and supercritical drying the intermediate material II in sequence to obtain an aerogel film.

[0045] In some embodiments, the present invention preferably adopts a tension-free winding method for the winding, which can effectively reduce the stretching of the polyimide aerogel film, prevent it from being thinned, and at the same time maintain the stability of the winding.

[0046] The present invention does not particularly limit the specific methods for carrying out the aging, the solvent replacement, and the supercritical drying. Those skilled in the art can select according to the known technical means in the art. However, in order to obtain an aerogel film product with better chemical stability, mechanical strength, and product thickness uniformity, the present invention provides a preferred specific implementation manner hereinafter.

[0047] According to a preferred embodiment of the present invention, the aging is carried out under airtight conditions, the aging temperature is 18 - 45 °C, preferably 20 - 30 °C; the time is 5 - 24 h, preferably 10 - 20 h. By using the aging method under the preferred conditions of the present invention, on the one hand, it can keep the nano-porous structure from collapsing due to the volatilization of organic solvents, resulting in a decline in product quality. On the other hand, the airtight container can effectively prevent the volatilization of organic solvents into the air, providing a good working environment for production.

[0048] According to a preferred embodiment of the present invention, anhydrous ethanol is used for the solvent replacement.

[0049] Currently, the wet gel film mainly adopts the gradient replacement method. Otherwise, it is extremely easy to cause changes in the wet gel structure or even collapse. However, the aerogel film prepared by the technical solution provided by the present invention has a uniform structure, a uniform molecular weight, and a complete gel network structure. The present invention can adopt the direct replacement method without causing changes in the aerogel structure, avoiding the generation of a large amount of mixed solvents, and facilitating the later solvent recovery and use. At the same time, the film material prepared by the present invention has a small thickness. Preferably, the thickness of the wet gel is 100 - 500 μm, and the solvent can enter the gel interior within a short time during replacement to complete the replacement.

[0050] According to a preferred embodiment of the present invention, the supercritical drying is CO2 supercritical drying, and the conditions for the CO2 supercritical drying are as follows: the temperature is 37 - 65 °C, and the pressure is 7.3 - 15 Mpa.

[0051] As described above, the second aspect of the present invention provides an aerogel film prepared by the method described in the first aspect above.

[0052] Preferably, the thickness of the aerogel film is 50 - 300 μm.

[0053] Preferably, the standard deviation of the thickness of the aerogel film is ≤ 6%.

[0054] Preferably, the light transmittance of the aerogel film is 80 - 90%, and the tensile strength is ≥ 1.5 MPa.

[0055] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the materials used are all commercially available products.

[0056] Polymer auxiliary film 1: Silicone oil is coated on one side of a PET film. The release force is 20 g / cm, the light transmittance is 95%, the tensile strength is 100 MPa, the thickness of the PET film is 100 μm, and it is purchased from Dongguan Ruixin Plastics Co., Ltd.

[0057] Polymer auxiliary film 2: Silicone oil is coated on one side of a PP film. The release force is 15 g / cm, the light transmittance is 85%, the tensile strength is 150 MPa, the thickness of the PP film is 70 μm, and it is purchased from Dongguan Ruixin Plastics Co., Ltd.

[0058] Polymer auxiliary film 3: Silicone oil is coated on one side of a PTFE film. The release force is 40 g / cm, the light transmittance is 75%, the tensile strength is 50 MPa, the thickness of the PTFE film is 150 μm, and it is purchased from Dongguan Ruixin Plastics Co., Ltd.

[0059] Polymer auxiliary film 4: Silicone oil is coated on one side of a PVC film. The release force is 50 g / cm, the light transmittance is 75%, the tensile strength is 50 MPa, the thickness of the PVC film is 100 μm, and it is purchased from Shenzhen Xinsheng Plastic Raw Materials Co., Ltd.

[0060] Polymer auxiliary film 5: Silicone oil is coated on both sides of a PET film. The release force is 20 g / cm, the light transmittance is 95%, the tensile strength is 100 MPa, the thickness of the PET film is 100 μm, and it is purchased from Dongguan Ruixin Plastics Co., Ltd.

[0061] Polymer auxiliary film D1: Silicone oil is coated on one side of a PET film. The release force is 70 g / cm, the light transmittance is 95%, the tensile strength is 100 MPa, the thickness of the PET film is 100 μm, and it is purchased from Dongguan Ruixin Plastics Co., Ltd.

[0062] The thickness, light transmittance, and tensile strength data of the above polymer auxiliary films are all self-tested, and the testing methods are as follows:

[0063] Thickness testing method: At the 1 m, 2 m, and 3 m positions at the roll head of the polymer auxiliary film, 3 points are tested at the left, middle, and right respectively, for a total of 9 points, and the average value is obtained, which is the thickness of the polymer auxiliary film.

[0064] Light transmittance testing method: Refer to ASTM D1003-21 standard.

[0065] Tensile strength testing method: Refer to GB / T 17911-2006 standard.

[0066] The aerogel slurries used in the following examples are all polyimide aerogel slurries and are prepared by the following method:

[0067] 1) Batching process

[0068] First, a part of the organic solvent (N-methylpyrrolidone) and diamine I (4,4-diaminodiphenyl ether) are added to the reaction kettle according to a set ratio. After stirring and mixing evenly, diamine II (2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl) and dianhydride monomer (3,3',4,4'-biphenyltetracarboxylic dianhydride) are added to the reaction kettle in sequence according to the ratio for the first reaction (900 rpm, 25 °C, 60 min). A part of the organic solvent accounts for 60% of the total mass of the organic solvent; the molar ratio of diamine I to diamine II is 2:1, and the molar ratio of amino group to anhydride group is 1:1;

[0069] The remaining part of the organic solvent and the cross-linking agent (1,3,5-tris(4-aminophenoxy)benzene) are added to mixing tank 1 according to the ratio, stirred and mixed evenly, and then the mixture in mixing tank 1 flows into the reaction kettle by gravity for contact reaction (300 rpm, 25 °C, 10 min) to obtain mixture I (where the organic solvent content is 90 wt%);

[0070] The dehydrating agent (acetic anhydride) and the catalyst (pyridine) are added to mixing tank 2 in sequence according to a molar ratio of 1:1, and then the mixture in mixing tank 2 flows into the reaction kettle by gravity for the second reaction (2000 rpm, 25 °C, 3 min). Vacuum degassing treatment is carried out synchronously during the stirring reaction process; an intermediate slurry is obtained; the molar ratio of the dehydrating agent to the dianhydride monomer is 8:1;

[0071] 2) Defoaming process

[0072] The intermediate slurry is introduced into a centrifugal defoaming machine. The revolution speed of the centrifuge is 2000 rpm and the rotation speed is 1600 rpm. It runs for 3 min to obtain the defoamed polyimide aerogel slurry.

[0073] Example 1

[0074] S1: Coating is carried out using a comma knife coater. Before coating, the surfaces of the knife and the coating roller should be cleaned, the gap between the comma knife and the coating roller should be adjusted, and then accurately calibrated with a feeler gauge or a laser thickness measuring instrument (the gap accuracy reaches ±0.01 mm). The polyimide aerogel slurry (viscosity is 5200 mPa·S) is introduced between two layers of polymer auxiliary films for coating and forming to obtain intermediate material I;

[0075] The polymer auxiliary film is obtained by coating silicone oil on the surface of the polymer film, and the side coated with silicone oil is in direct contact with the aerogel slurry.

[0076] S2: Intermediate material I is sandwiched between two layers of polymer auxiliary films and enters the oven for drying and curing treatment by means of gradient heating to obtain intermediate material II.

[0077] S3: Unwind and wind the three-layer film of intermediate material II without tension. Place the obtained wet gel film in an aging kettle, keep it airtight, and let it stand at 30 °C for 12 h. Then soak it in absolute ethanol for solvent replacement. During the replacement process, change the absolute ethanol until the ethanol content in the replaced solvent is ≥99 vol%. Then place it in a CO2 supercritical drying equipment for drying treatment to obtain a polyimide aerogel film product (the set target thickness is 100 μm).

[0078] For the specific types of raw materials and process parameters, please refer to those listed in Table 1.

[0079] Examples 2 and 3

[0080] The same process as in Example 1 is adopted, except that the types of raw materials and process parameters are different. For details, please refer to those listed in Table 1, and a polyimide aerogel film is prepared.

[0081] Example 4

[0082] The same process as in Example 1 is adopted, except that polymer auxiliary film 1 is replaced with polymer auxiliary film 4 with the same area dosage, and the rest remains unchanged, and a polyimide aerogel film is prepared.

[0083] Example 5

[0084] The same process as in Example 1 is adopted, except that polymer auxiliary film 1 is replaced with polymer auxiliary film 5 with the same area dosage, and the rest remains unchanged, and a polyimide aerogel film is prepared.

[0085] During the coating and winding process of preparing polyimide aerogel film with a polymer auxiliary film coated with silicone oil on both sides, it is easy to slip, resulting in uneven winding, and further causing shrinkage during the unwinding process after drying, which has an adverse impact on the quality stability of the product to a certain extent.

[0086] Comparative Example 1

[0087] The same process as in Example 1 is adopted, except that polymer auxiliary film 1 is replaced with polymer auxiliary film D1 with the same area dosage, and the rest remains unchanged, and a polyimide aerogel film is prepared.

[0088] Comparative Example 2

[0089] The same process as in Example 1 is adopted, except that the polyimide aerogel slurry is coated between PET films without silicone oil coating, and the rest remains unchanged; a polyimide aerogel film is prepared.

[0090] Table 1

[0091]

[0092]

[0093] Test Example

[0094] Thickness standard deviation test method: The thickness of the target film is h0. Eight points of the thickness of the prepared film are selected, and the standard deviation is calculated according to the standard deviation formula, and the average value is recorded as h1.

[0095] Transmittance test method for aerogel film: Refer to ASTM D1003-21 standard.

[0096] Tensile strength test method for aerogel film: Refer to GB / T 17911-2006 standard.

[0097] See Table 2 for specific results.

[0098] Table 2

[0099]

[0100] It can be seen from the above results that the aerogel film products prepared by the technical solution provided by the present invention have uniform thickness, and the structural consistency and stability of the two surfaces of the film products are also greatly improved, and they have more excellent optical and mechanical properties.

[0101] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the technical concept scope of the present invention, various simple modifications can be made to the technical solution of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.

Claims

1. A forming method of an aerogel film, characterized in that, The method includes: (1) Introducing an aerogel slurry between two layers of polymer auxiliary films for coating and forming to obtain intermediate material I; the polymer auxiliary film is obtained by coating silicone oil on the surface of a polymer film, and the side coated with silicone oil is in direct contact with the aerogel slurry; (2) Curing the intermediate material I; The release force of the polymer auxiliary film is 15 - 50 g / cm; The light transmittance of the polymer auxiliary film is 75% - 95%, and the tensile strength is 50 - 150 MPa.

2. The method according to claim 1, characterized in that, The thickness of the polymer film is 50 - 150 μm.

3. The method according to claim 1 or 2, characterized in that, Use a polymer auxiliary film with silicone oil coated on one side, and make the side coated with silicone oil be in direct contact with the aerogel slurry to perform the coating and forming operation.

4. The method according to claim 1 or 2, characterized in that, The aerogel slurry is a polyimide aerogel film slurry.

5. The method according to claim 4, wherein The viscosity of the aerogel slurry is 500 - 12000 mPa·S.

6. The method according to claim 4, characterized in that The polymer film is selected from at least one of PET film, PP film, PTFE film, PE film, PPS film, and PI film.

7. The method according to claim 1 or 2, characterized in that In step (1), the coating and forming method is a doctor blade coating method and / or a roll coating method; The temperature of the coating and forming is -8°C to 25°C.

8. The method according to claim 1 or 2, characterized in that, In step (2), the curing treatment adopts a gradient heating method, and the temperature interval between adjacent gradients is 5 - 10°C; And / or, in step (2), the end temperature of the curing treatment is 60 - 70°C, and the treatment time for each temperature gradient is independently selected from 3 - 10 min.

9. An aerogel film prepared by the method according to any one of claims 1 - 8.

10. The aerogel film according to claim 9, wherein The standard deviation of the thickness of the aerogel film ≤ 6%; And / or, the light transmittance of the aerogel film is 80% - 90%, and the tensile strength is ≥ 1.5 MPa.